USING PICTURE-SERIES BASED INSTRUCTION TO IMPROVE SPEAKING AND WRITING ACHIEVEMENTS OF THE EFL UNDERGRADUATE STUDENTS - Jaya Nur Iman; Nike Angraini (Global Expert: Jurnal Bahasa dan Sastra, 2016)
Speaking and writing skills are very prominent for the students to actively interact and to get involved in spoken and written communication. However, these are regarded as difficult skills to master by the students. The researchersthen would like to carry out the research in terms of using picture-series to cope with the students’ speaking and writing problem. The objective of this research were: (1) to find out whether picture-series significantly improve the speaking and writing achievement of the EFL undergraduate students, (2) to find out the significant difference in speaking and writing achievement between the students who were taught by using picture series and those who were not.  A quasi-experimental study of non-equivalent pretest- posttest control group design or comparison group design was used in this research. The population of this research was all undergraduate students of Civil Engineering study program of Indo Global Mandiri University in the academic year of 2014/2015. Forty students were taken as sample and selected by using purposive sampling technique in which each group consisted of 20 students, respectively. The findings showed that (1) there was a significant improvement on the speaking and writing achievement of the experimental group where the tobtained of the speaking and writing achievement were 12.197 (p<0.000) and 18.710 (p<0.000), (2) there was also a significant difference between the speaking writing and achievement of the experimental and control group where tobtained were 2.916 (p<0.000) and 3.949 (p<0.000). Therefore, it could be concluded that the picture series-based instruction statistically and significantly improves the speaking and writing achievement of the EFL undergraduate students. Key words: picture series, speaking achievement, writing achievement